Hirsutism and oligomenorrhea are appropriate screening criteria for polycystic ovary syndrome in adolescents. (3rd August 2015) - Villarroel, Claudio; López, Patricia; Merino, Paulina M.; Iñiguez, Germán; Sir-Petermann, Teresa; Codner, Ethel
Abstract: We evaluated the association of hirsutism and oligomenorrhea (persistent menstrual cycles > 45 days) as screening criteria for the detection of biochemical hyperandrogenism (BH) and polycystic ovaries (PCOM) during adolescence and determined which androgens, granulosa cell hormone, ultrasonographic parameters have the best association with polycystic ovary syndrome (PCOS). Hirsute girls with oligomenorrhea ( N = 26 Hirs/Oligo group) and non-hirsute girls with regular cycles ( N = 63, C group) were studied. Prevalence of BH and PCOM, diagnostic performance of androgens and ultrasound parameters for PCOS diagnosis were analyzed. BH and PCOM prevalence were higher in the Hirs/Oligo girls than in the C girls (76.9% versus 25.5%; 92.3% versus 33.3%, respectively; p < 0.0001). A complete PCOS phenotype (Hirs/Oligo with BH and PCOM) was observed in 73.1% of the Hirs/Oligo group. The presence of both BH and PCOM was observed in 7.9% of the C group. The parameters with the best diagnostic performance were free androgen index ≥6.1, testosterone ≥2.4 nmol/L, follicle number ≥12 and ovarian volume ≥10 ml anti-Müllerian hormone (AMH) exhibited a low diagnostic accuracy. Hirsutism and persistent menstrual cycle over 45 days are highly associated with BH and PCOM suggesting that the presences of both criteria are necessary for the diagnosis of PCOS during adolescence. Chinese abstract: 我们评估多毛合并月经稀发（持续的月经周期超过45天）作为生化高雄激素（BH）和青春期多囊卵巢（PCOM）筛选标准的情况，并确定雄激素，颗粒细胞激素，超声参数中哪个与多囊卵巢综合征（PCOS）联系最为密切。本文研究了多毛合并月经稀发的女孩（N=26 多毛/月经稀发组）和非多毛并且月经规律女孩（N=63 C组）BH和PCOM的患病率，并分析了雄性激素和超声参数对PCOS的诊断性作用。BH和PCOM在多毛/月经稀发女孩组的患病率高于C 组女孩（分别是76.9%和25.5%；92.3%和33.3%；P＜0.0001）。73.1%的多毛/月经稀发组患者呈现了一个完整的PCOS表型（多毛/月经稀发合并BH和PCOM）。仅有7.9%的C组患者出现了BH和PCOM。最好的诊断性参数是游离雄激素指数≥6.1，睾酮≥2.4 nmol/L，卵泡数≥12和卵巢体积≥10ml, 而抗苗勒管激素（AMH）诊断准确性低。多毛和持续性月经周期超过45天与BH和PCOM高度相关表明了这两个标准在诊断青春期PCOS中是必要的。